2023
DOI: 10.3389/fnagi.2023.1086487
|View full text |Cite
|
Sign up to set email alerts
|

Whole body-electromyostimulation effects on serum biomarkers, physical performances and fatigue in Parkinson’s patients: A randomized controlled trial

Abstract: BackgroundWhole-body electromyostimulation (WB-EMS) was never previously applied to Parkinson’s disease (PD) patients. This randomized controlled study aimed to find the most effective and safe WB-EMS training protocol for this population.MethodsTwenty-four subjects (age: 72.13 ± 6.20 years), were randomly assigned to three groups: a high-frequency WB-EMS strength training group (HFG) (rectangular stimulation at 85 Hz, 350 μs, 4 s stimulation/4 s rest), a low-frequency WB-EMS aerobic training group (LFG) (rect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(56 citation statements)
references
References 67 publications
0
56
0
Order By: Relevance
“…The NRCT of Mori et al ( 24 ) addressed Huntington patients during dialysis with WB-EMS-application for 6 weeks 7 . While di Cagno et al ( 13 ) observed no adverse effects; unfortunately Mori et al ( 24 ) did not report unintended effects of WB-EMS application.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The NRCT of Mori et al ( 24 ) addressed Huntington patients during dialysis with WB-EMS-application for 6 weeks 7 . While di Cagno et al ( 13 ) observed no adverse effects; unfortunately Mori et al ( 24 ) did not report unintended effects of WB-EMS application.…”
Section: Resultsmentioning
confidence: 96%
“…Unfortunately, only a few studies focused on cohorts with diseases of the nervous system ( 13 , 24 ). The high-quality RCT of di Cagno et al ( 13 ) focused on stage 1 (mild) to 3 (moderate) Parkinson's disease in 50–80 years old patients for 12-week. The NRCT of Mori et al ( 24 ) addressed Huntington patients during dialysis with WB-EMS-application for 6 weeks 7 .…”
Section: Resultsmentioning
confidence: 99%
“…The quality of all trials was assessed. Three studies [ 51 , 52 , 53 ] were categorized as “good”, one trial [ 54 ] was categorized as “fair”, and one trial was categorized as “poor” [ 55 ]. Table 2 shows individual results for each of the 14 NIH quality criteria questions used to assess the methodological quality and make an informed decision about the possible risk for bias of each of the included trials, and it provides numerical results to assess the total methodological quality score and rating.…”
Section: Resultsmentioning
confidence: 99%
“…The trials were published between 2013 and 2023, and a total of 216 participants with PD contributed to the articles included in this systematic review. Three trials [ 52 , 54 , 55 ] conducted a moderate-intensity exercise program, and two trials [ 51 , 53 ] conducted a vigorous-intensity exercise program according to standards for exercise intensity articulated by Liguori and the American College of Sports Medicine (ACSM) [ 56 ]. Additionally, exercise frequencies ranged from two to five sessions per week, and intervention duration ranged from 20 to 180 min per session over a period of four to twelve weeks.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, there are three essential conditions that must be considered when designing a physical protocol with the goal of reducing blood pressure and, consequently, medication intake: a long-term commitment to regular PA; good adherence to the exercise protocol; and appropriate volume, intensity, and modality of exercise [28]. Enhancing enjoyment and motivation through various strategies, such as group exercise or the utilization of technological equipment, could facilitate long-term adherence to physical activity programs for the elderly [45,46].…”
Section: Discussionmentioning
confidence: 99%